Implementing performance measurement systems: Indonesian local government under pressure - Akbar, R.; Pilcher, Robyn; Perrin, B. (Emerald Group Publishing Ltd., 2015)
Purpose - This paper aims to explore the perceived drivers behind the implementation of performance measurement systems (PMSs) in Indonesian local government (ILG). It analytically assesses Indonesia's attempt to introduce PMSs by addressing three research questions: Do organisations in developing countries actually use PMSs to aid decision-making and help plan for future performance improvement? (RQ1) Do the three isomorphic pressures exist in the development and use of PMSs? (RQ2) and If institutional isomorphism is evident, can accountability exist within the development and use of PMSs given these pressures? (RQ3). Design/methodology/approach - This research explores the perceived drivers behind the implementation of performance measurement systems (PMSs) in Indonesian local government (ILG). It analytically assesses Indonesia's attempt to introduce a PMS by addressing three research questions: RQ1 Do organisations in developing countries actually use PMSs to aid decision-making and help plan for future performance improvement? RQ2 Do the three isomorphic pressures exist in the development and use of PMSs? and RQ3 If institutional isomorphism is evident, can accountability exist within the development and use of PMSs given these pressures. Findings - Results determined that although employees perceived coercive isomorphism as being a driver of ILG compliance with President B.J. Habibie's presidential instruction (Inpres No. 7/ 1999), the Laporan Akuntabilitas Kinerja Institusi Pemerintah/Performance Accountability Report of State Apparatus (known as LAKIP), many councils were still not reporting and those who were, were not doing it well. Many councils lacked management motivation, with some choosing to merely mimic (mimetic isomorphism) what others were doing. Better-resourced councils made use of external consultants or local universities where knowledge was shared (normative isomorphism). Practical implications - An understanding of factors influencing the development and use of performance measures, in turn, can be used not only to improve PMSs in the future but to improve the quantity and quality of LAKIP reporting. Originality/value - The theoretical development and interpretation of this research is drawn from institutional theory with a major contribution being that it provides an in-depth conceptual overview and understanding of factors influencing the development and use of performance measures. Further, it fills a gap in the literature exploring PMSs and accountability in a developing country - in this case, Indonesia.